Essentials of Public Sector Reform: a Case Study of Croatia - Farhad Analoui (Romanian Journal of European Affairs)
This paper explores the challenges faced by developing countries and countries in transition in their attempt at reforming the inherited bureaucratic public service. The paper explores how the public sector in Croatia has managed to come this far after the turbulent years of political and technocratic dislocation. Croatia is determined to reform its public sector to become eligible for joining the European Union (EU) in near future. This has posed a major challenge for top senior officials and consultants alike. Adopting ‘action research’ as both a methodology and a strategy, a programme of intervention for change was designed and implemented in the Ministry of Finance. The overall results suggest that for the successful implementation of public sector reforms in the 21st century, attention should focus on strategic issues including systems thinking, HRMD, behavioural and attitudinal change, skills and competencies development and, above all, honest and responsible transformational leadership.